1989
DOI: 10.1128/iai.57.3.817-822.1989
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation by fibronectin of macrophage-mediated phagocytosis of Pseudomonas aeruginosa

Abstract: In a previous investigation it was determined that Pseudomonas aeruginosa cells taken directly from a mouse in vivo growth system were significantly more susceptible to nonopsonic phagocytosis by macrophages than were similar cells after being washed in buffer (N.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 19 publications
(14 reference statements)
1
19
0
Order By: Relevance
“…Fibronectin is expressed by various cell types, including macrophages, endothelial cells, and smooth muscle cells (23,24), and it is implicated in the modulation of immune cell functions (23,25,26). The activation of immune cells, such as macrophages and T lymphocytes, increases their attachment to fibronectin, which suggests an important function of fibronectin in host defenses (24).…”
Section: Discussionmentioning
confidence: 99%
“…Fibronectin is expressed by various cell types, including macrophages, endothelial cells, and smooth muscle cells (23,24), and it is implicated in the modulation of immune cell functions (23,25,26). The activation of immune cells, such as macrophages and T lymphocytes, increases their attachment to fibronectin, which suggests an important function of fibronectin in host defenses (24).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial strains and growth conditions. The P. aeruginosa strains used were the wild-type strain H103 (15) and its nonmotile, rough, piliated derivative H237, kindly provided by A. Kropinski (Department of Microbiology, Queen's University, Ontario, Canada) and the PAK parental wildtype strain and its rpoN mutant derivative NIG, which * Corresponding author. carries a gentamicin resistance cassette in the rpoN gene (4), kindly provided by S. Lory (Department of Microbiology, University of Washington, Seattle).…”
Section: Methodsmentioning
confidence: 99%
“…Pseudomonas aeruginosa is susceptible to phagocytic killing by macrophages in both the presence and absence of opsonins, such as specific antibody (7,15,26). It was previously demonstrated that exposure of macrophages to fibronectin resulted in subsequent enhancement of nonopsonic phagocytosis of P. aeruginosa (14,15,29). This occurred regardless of the fibronectin source and with the P388D1 macrophage cell line, with nonelicited mouse peritoneal macrophages, and with human monocyte-derived macrophages (15).…”
mentioning
confidence: 97%
See 2 more Smart Citations